Odziv na dezmopresin (DDAVP) pri von Willebrandovi bolezni: preoperativno preverjanje - Andoljšek, Dušan (Zdravniški vestnik, 2008)
Background The principle of treatment or prevention of bleeding in von Willebrand disease (vWd) is correction of dual plasma deficiency of von Willebrand factor (vWF) and factor VIII (F VIII). This can be achieved by desmopressin (DDAVP) or plasma fractions. DDAVP effect was tested in von Willebrand patients before surgical procedure. Methods DDAVP test was done in 13 vWd patients (type 1) by slow infusion of DDAVP (0.3 ug/bw Minirin, Ferring) in 100 ml of saline. Before, after 1, 4 hours venous blood sample wastaken for F VIII:C, vWF:Rco, vWF:CBA, vWF:Ag. Results After 1 hour, preinfusion levels comparison showed, F VIII:C, vWF:CBA, vWF:Ag were 2-4 timeshigher, vWF:RCo 2-3 times higher. 4 hours later all the levels were one third to one fourth lower but still high enough to prevent bleeding. Conclusions DDAVP raises vWF in vWd patients (except type 3) and has efficacious hemostatic response as it prevents or stop bleeding. Using DDAVP test, 2-4 times higher levels of F VIII and vWF were noticed 1 hour after DDAVP infusion. The data can help us to decide the optimal treatment to prevent and stop bleeding in vWd patients.
Keywords: Desmopressin; Dezmopresin; Drug Therapy; Factor Viii; Faktor VIII; hematologija; krvavitev; krvne bolezni; Predoperativna oskrba; Preoperative Care; therapy; Von Willebrand Factor; von Willebrandov faktor; Von Willebrand'S Disease; zdravljenje